The impact evaluation of income redistribution on social inequality in Indonesia: Propensity score matching approach - Muntazar, Nazril (Privietlab, 2026)
While Indonesia has implemented a wide array of social assistance and subsidy programs to counteract poverty and inequality, the redistributive impact of these policies remains questionable. This study presents a rigorous and critical examination of the causal effect of income redistribution through cash transfers and subsidies on social inequality, employing Propensity Score Matching (PSM) to control for selection bias. Utilizing data from the nationally representative SUSENAS (2019-2022) across the pre-, during, and post-pandemic periods, this analysis compared beneficiary and non-beneficiary households across various socioeconomic dimensions. In contrast to previous descriptive work, our findings provide strong evidence of the short-term redistribution effects on per-capita consumption and the household Gini index. The results indicate that consumption increased on average by 8.3 percent, and inequality fell significantly, with some degree of spatial heterogeneity. The most significant effects on inequality were observed in Western Indonesia, whereas the Eastern areas experienced minor effects. The analysis reveals policy-relevant heterogeneity, with larger benefits for female-headed households and those receiving multiple programs than for male-headed households. This study contributes to the existing literature by (1) using PSM to assess the cross-program redistributive effect, (2) illustrating the spatial disparities of implementation, and (3) exploring complementarity among types of assistance. Policy implications call for integrated targeting systems, real-time microdata surveillance, and adaptive program design that is region-specific. Redistribution is not enough; substantive reforms must support fiscal efforts for long-term social justice.